Gambaran Kadar Serum Glutamic Pyruvic Transaminase (SGPT) Pada Penderita Tuberculosis Pengobatan 6 Bulan – 1 Tahun - Wa Ode Rustiah; Muawanah Muawanah; Rahmawati Rahmawati; Nurul Ni’ma Azis; Novita Rahman (Lontara Journal of Health Science and Technology, 2022)
Tuberculosis (TB) is an infectious disease caused by the bacteria of Mycobacterium tuberculosis. A person who has been diagnosed with active TB (TB that affects the lungs and causes symptoms of coughing up blood, night sweats, weight loss, fever and chest pain), will be given a TB drug package (OAT) that must be taken for six months, where This drug is a combination of several antibiotics. TB treatment is divided into 2 phases, namely the intensive phase (2-3 months) and the continuation phase (4-6 months). The combination of drugs used consists of a combination of the main and additional drugs. In the treatment of TB, OAT is the main type of drug used. The most serious side effect of using OAT is hepatotoxic. Hepatotoxicity is a reaction to exposure to substances that can cause liver damage. Liver function tests can be done through the SGPT test. The type of this research is descriptive, with the aim of providing an overview of the results of determining Serum Glutamic Pyruvic Transaminase (SGPT) levels in TB patients who undergo treatment for 6 months - 1 year, by taking 8 samples of serum from TB patients, using the Kinetic method on the Biochemical Photometer BC153. The results showed that there were 3 samples that had increased levels of SGPT and the other 5 samples did not experience an increase in levels of SGPT (normal). Giving OAT does not significantly cause SGPT levels in tuberculosis patients to increase, but long-term administration of OAT can affect the increase in SGPT in tuberculosis patients.